Cam device
By using brass cast alloy matrix and CR-FE-SI system metal inter-metal compounds in the sliding material of the cam device, and to bury the solid lubricant in the sliding surface, the cam device is solved The problem of insufficient durability achieves higher wear resistance and durability, and high -precision processing performance under high load conditions.
Patent Information
- Application Number
- CN202380046032.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-21
- Filing Date
- 2023-07-04
- Publication Date
- 2025-01-21
AI Technical Summary
In the processing of high-strength materials, existing cam devices have insufficient wear resistance and durability, resulting in poor performance in low-speed and high-load sliding environments.
Use brass cast alloy as a substrate, which contains the sliding material of the CR-FE-SI series of inter-metal compounds. The nano-indentation of the CR-FE-SI is more than 20GPa and below 28GPa, and it is buried in the sliding surface. Solid lubricant.
It significantly improves the wear resistance and durability of the cam device, reduces the friction coefficient, prolongs the service life of sliding materials, and maintains high -precision processing performance under high load conditions.
Smart Images

Figure CN119343471A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a cam device. Background Art
[0002] Cam devices are used in hydraulic and other press machines, and their sliding materials are used under low-speed, high-load, and harsh sliding environment conditions. Therefore, cam devices have become applications where their sliding materials need to have wear resistance and low friction properties. For sliding materials assembled in cam devices, the importance of friction and wear properties has been confirmed in terms of initial running-in performance, but the adaptability of the brass casting alloys used has not been studied in detail.
[0003] Patent document 1 states that the hardness of the sliding surface of the cam holder is set to be softer than the hardness of the sliding surface on the cam slider side, and that the initial running-in is completed earlier by setting the hardness of the sliding surface in the cam driver to be softer than the hardness of the sliding surface of the cam slider.
[0004] Patent document 2 states that by making the amount of wear between the cam bracket sliding surface and the cam slider sliding surface greater than the amount of wear between the cam driver sliding surface and the cam slider sliding surface, the contact area caused by running-in during the initial wear period is expanded to prevent excessive contact surface pressure.
[0005] Patent Document 3 describes that a brass matrix is limited to a β phase and contains Fe-based silicides such as Fe-Cr-Si-based intermetallic compounds, but details regarding application to a cam device are not known.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2011-140048;
[0009] Patent Document 2: Japanese Patent Application Publication No. 2015-27702;
[0010] Patent document 3: Japanese Patent Application Publication No. 2010-265500. Summary of the invention
[0011] Technical problem to be solved by the invention
[0012] The sliding material used for the cam device is mainly a JIS high-strength brass cast alloy represented by CAC303. In recent years, the wear resistance and durability of the cam device have become problems in the processing of high-strength materials such as high-strength steel materials that are often used for automobile outer panels.
[0013] The present invention has been made to solve the problems in the prior art, and an object of the present invention is to provide a cam device having improved wear resistance and durability.
[0014] Solutions to technical problems
[0015] The present invention is a cam device having a sliding material, wherein the sliding material has: a substrate, which is composed of a brass-based casting alloy; and a Cr-Fe-Si-based intermetallic compound, which is contained in the substrate and has a nanoindentation hardness of 20 GPa or more and 28 GPa or less in the area where the Cr-Fe-Si-based intermetallic compound is exposed.
[0016] Effects of the Invention
[0017] According to the present invention, it is possible to provide a cam device having improved wear resistance and durability. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a diagram of a cam mechanism.
[0019] Figure 2 This is a diagram related to the operation of the cam device.
[0020] Figure 3 This is a diagram showing a solid lubricant buried in a sliding material.
[0021] Figure 4 It is a figure which shows the cross-sectional structure of a sliding material.
[0022] Figure 5 This is a SEM image of Cr-Fe-Si intermetallic compounds in the sliding material.
[0023] Fig. 6A is the nanoindentation hardness determination graph; Figure 6B This is a graph showing the measurement of nanoindentation hardness.
[0024] Figure 7 It is a diagram of Fe-Al intermetallic compounds.
[0025] Figure 8 is a diagram of a reciprocating sliding test apparatus.
[0026] Fig. 9 It is a graph showing the results of the reciprocating sliding test.
[0027] Fig.10 is a diagram of a cam sliding test apparatus.
[0028] Fig.11 It is a graph showing the wear curve of the sliding material of the cam device.
[0029] Fig.12It is a graph showing the wear curve of the sliding material of the cam device.
[0030] Fig.13 This is a diagram of the cam device placed below.
[0031] Fig.14 is a diagram of a roller cam device. DETAILED DESCRIPTION
[0032] Hereinafter, the cam device according to the embodiment will be described in detail. However, the present invention is not limited to the embodiment.
[0033] Figure 1 1 is a perspective exploded view showing a cam device according to an embodiment. Figure 1 As shown, the cam device 1 of the embodiment includes a cam holder 2 , a cam slider 3 , a cam driver 4 , and a return elastic member 5 .
[0034] The cam holder 2 includes a cam holder sliding material 2b having a cam holder sliding surface 2a and a cam holder base 2c. The cam holder sliding material 2b is attached to the mounting surface of the cam holder base 2c by bolts. Thus, the cam holder sliding material 2b can be easily replaced.
[0035] Since the cam bracket base does not need to be removed from the mold when the sliding material is worn, it has the advantages of shortening the time and cost of replacement compared to a structure in which the cam bracket sliding material and the cam bracket base are integrated. Figure 1 The cam support sliding material 2b shown is in the shape of a flat plate, but the shape is not limited to this as long as it has a sliding function.
[0036] The cam slider 3 includes a cam slider sliding surface 3a on the cam holder side that is in sliding contact with the cam holder sliding surface 2a of the cam holder 2, a cam slider sliding surface 3b on the cam driver side, and a tool mounting surface 3e. The cam slider 3 moves relative to the cam holder 2 by the cam slider sliding surface 3a on the cam holder side contacting the cam holder sliding surface 2a, and the cam slider sliding surface 3b on the cam driver side contacting the cam driver sliding surface 4a described later, thereby moving relative to the cam driver 4 in a predetermined processing direction. A processing tool (for example, a punch for drilling, a bending tool, etc.) not shown in the figure is mounted on the tool mounting surface 3e.
[0037] The cam driver 4 includes a cam driver sliding material 4b and a cam driver base 4c. The cam driver sliding material 4b includes a cam driver sliding surface 4a that contacts the cam driver side cam slider sliding surface 3b. The cam driver 4 forcibly moves the cam slider 3 in a predetermined processing direction by contacting the cam driver sliding surface 4a with the cam driver side cam slider sliding surface 3b. The cam driver sliding material 4b is mounted on the mounting surface of the cam driver base 4c by bolts. Thus, the cam driver sliding material 4b can be easily replaced.
[0038] Since the cam driver base does not need to be removed from the mold when the sliding material wears, it has the advantages of shortening the time and cost of replacement compared to a structure in which the cam driver sliding part and the cam driver base are integrated. Figure 1 The cam actuator sliding material 4b shown has a V-shaped cross section, but is not limited thereto and may also be a flat plate shape, a convex cross section shape, or the like as long as it has a sliding function.
[0039] exist Figure 1 In the figure, the cam bracket 2 and the cam driver 4 have a cam bracket sliding material 2b and a cam driver sliding material 4b, respectively, but are not limited to this. The cam slider 3 has a cam bracket side cam slider sliding material 3f (not shown) and a cam driver side cam slider sliding material 3g (not shown) that can be installed. The cam bracket side cam slider sliding surface 3a or the cam driver side cam slider sliding surface 3b of the cam slider 3 can also be the sliding surface of the cam bracket side cam slider sliding material 3f and the cam driver side cam slider sliding material 3g that can be installed.
[0040] In addition, the cam bracket sliding material 2b, the cam driver sliding material 4b, the cam bracket side cam slider sliding material 3f and the cam driver side cam slider sliding material 3g do not need to be separate bodies that can be installed on the main body, and can also be integrated with the main body (or part of the main body).
[0041] As the restoring elastic member 5, for example, a coil spring or a pneumatic cylinder can be used. Figure 1 An example of using a pneumatic cylinder is shown in FIG. The cam slider 3 is returned to the initial position by the elastic force of the return elastic member 5 .
[0042] Figure 2 is a diagram showing the operation of the cam device. Figure 2 In (A) to (C), the operation of the cam device 1 is shown using cross-sectional views. The restoring elastic member 5 is a coil spring. Figure 2 From the state (initial state) shown in (A), the cam holder 2 and the upper die of the die (not shown) are moved from the top dead center ( Figure 2 (A)) Downward dead center ( Figure 2 (C)) moves in the up-down direction, so that the cam slider 3 moves in the processing direction. The processing tool T provided on the tool mounting surface 3e of the cam slider 3 moves in the processing direction to perform drilling processing and bending processing on the workpiece provided in the mold.
[0043] When the cam device 1 is in motion, wear due to sliding occurs on the cam support sliding surface 2a and the cam driver sliding surface 4a. Here, high precision is required for relative position adjustment between the processing tool and the workpiece, so the wear on the cam support sliding surface 2a and the cam driver sliding surface 4a is required to be small.
[0044] Figure 3 This is a diagram showing an enlarged portion of a sliding surface (cam holder sliding surface 2a, cam driver sliding surface 4a, cam holder side cam slider sliding surface 3a, or cam driver side cam slider sliding surface 3b) of a sliding material (cam holder sliding material 2b, cam driver sliding material 4b, cam holder side cam slider sliding material 3f, or cam driver side cam slider sliding material 3g) in which a solid lubricant is embedded in a brass-based cast alloy.
[0045] As shown in the figure, on the sliding surface, a solid lubricating material 2d (4d, 3h) with a circular cross section is distributed on the matrix 2e (4e, 3i). The solid lubricant 2d (4d, 3h) is, for example, graphite. The buried solid lubricant forms a self-lubricating effect under mixed lubrication, and shows good lubrication performance even in an environment accompanied by impact that is difficult to form an oil film. In addition, the sliding surface is supported by the matrix and hard particles. The solid lubricant is firmly attached to the Cr-Fe-Si system intermetallic compound as hard particles to form a lubricating film, which has the effect of reducing the friction coefficient. As a result, the progress of wear can be delayed (reducing the friction speed) and the service life can be extended by the solid lubricant and hard particles. In addition, the solid lubricant is also transferred and slid to the surface of the matrix.
[0046] Figure 4 1 is a diagram showing a cross-sectional structure of a portion of a sliding material (cam holder sliding material 2b, cam driver sliding material 4b, cam holder side cam slider sliding material 3f, or cam driver side cam slider sliding material 3g) according to an embodiment. The cam holder sliding material 2b, cam driver sliding material 4b, cam holder side cam slider sliding material 3f, and cam driver side cam slider sliding material 3g have the same cross-sectional structure, and therefore, the cam holder sliding material 2b, cam driver sliding material 4b, cam holder side cam slider sliding material 3f, and cam driver side cam slider sliding material 3g have the same cross-sectional structure. Figure 4 The structures of these sliding materials are also explained. Figure 4 The relationship between the sizes of the solid lubricant and the Cr-Fe-Si based intermetallic compound is for illustration only and does not represent a strict size relationship.
[0047] Here, the cam bracket sliding material 2b has a matrix 2e, a Cr-Fe-Si intermetallic compound 2f, and a solid lubricating material 2d, the cam driver sliding material 4b has a matrix 4e, a Cr-Fe-Si intermetallic compound 4f, and a solid lubricating material 4d, the cam bracket side cam slider sliding material 3f has a matrix 3i, a Cr-Fe-Si intermetallic compound 3j, and a solid lubricating material 3h, and the cam driver side cam slider sliding material 3g has a matrix 3i, a Cr-Fe-Si intermetallic compound 3j, and a solid lubricating material 3h.
[0048] Figure 4 The structure of the intermetallic compound observed from a cross section perpendicular to the sliding surface is shown. The cam support sliding material 2b, the cam driver sliding material 4b, the cam support side cam slider sliding material 3f, and the cam driver side cam slider sliding material 3g respectively have bases 2e, 4e, and 3i, Cr-Fe-Si based intermetallic compounds 2f, 4f, and 3j, and solid lubricants 2d, 4d, and 3h.
[0049] The base bodies 2e, 4e and 3i are brass-based casting alloys, and provide the cam support sliding material 2b, the cam driver sliding material 4b, the cam support side cam slider sliding material 3f and the cam driver side cam slider sliding material 3g with shapes and mechanical strengths corresponding to the uses.
[0050] The cam support sliding material 2b, the cam driver sliding material 4b, the cam support side cam slider sliding material 3f, and the cam driver side cam slider sliding material 3g of the embodiment respectively contain (Cr,Fe)3Si as Cr-Fe-Si system intermetallic compounds 2f, 4f, and 3j having Cr as the main component. The Cr-Fe-Si system intermetallic compounds 2f, 4f, and 3j typically have (Cr 0.85 Fe 0.15 )3Si structure.
[0051] The Cr-Fe-Si intermetallic compounds 2f, 4f and 3j are compounds composed of Cr, Fe and Si. The Cr-Fe-Si intermetallic compounds 2f, 4f and 3j of the embodiment have a structure of (Cr, Fe)3Si. The Cr-Fe-Si intermetallic compounds 2f, 4f and 3j each have a curved shape with rounded corners.
[0052] The plurality of Cr-Fe-Si intermetallic compounds 2f, 4f and 3j respectively included in the matrix 2e, 4e and 3i are bonded to each other, thereby forming a three-dimensional structure in which the plurality of Cr-Fe-Si intermetallic compounds 2f, 4f and 3j are respectively connected. The Cr-Fe-Si intermetallic compounds 2f, 4f and 3j respectively included in the cam support sliding material 2b, the cam driver sliding material 4b, the cam support side cam slider sliding material 3f and the cam driver side cam slider sliding material 3g of the embodiment have a nanoindentation hardness of 20 GPa or more and 28 GPa or less.
[0053] Regarding the identification and atomic bonding ratio of Cr-Fe-Si intermetallic compounds 2f, 4f and 3j, the atomic bonding ratio of the compound is calculated from the atomic % composition based on SEM-EDS point analysis. For example, in the case of a simple Mn silicide, it is known that the bonding ratio of Mn:Si=5:3 is a compound with a chemical structure of Mn5Si3.
[0054] The description of the intermetallic compound is the same as that of the general alloy components, and is described in order from the most abundant component, and is described as a Mn-Si system intermetallic compound. Therefore, Cr-Fe-Si system intermetallic compounds 2f, 4f and 3j represent compounds composed of Cr, Fe and Si with Cr as the main component.
[0055] The present inventors have confirmed that when the compound is ternary as a Mn-Fe-Si intermetallic compound, its main structure does not change to Mn5Si3, but a part of Mn is replaced by (Mn x ,Fe y ) (where x+y=1), and the substitution ratio is clarified. That is, by using these measuring devices and introducing the idea of determining the chemical structure, the accurate chemical structure can be known.
[0056] Conventionally, intermetallic compounds are often evaluated based on their cross-sectional shapes. However, in the case of friction and wear, it is necessary to understand the three-dimensional crystal morphology of the compound in accordance with the progress of wear.
[0057] The present inventors have developed an etching method for dissolving the brass matrix 2e, 4e and 3i and leaving only the Cr-Fe-Si intermetallic compounds 2f, 4f and 3j. Thus, the three-dimensional crystal morphology of the Cr-Fe-Si intermetallic compounds 2f, 4f and 3j can be observed by SEM (secondary electron imaging) ( Figure 5 ).
[0058] The hardness of the Cr—Fe—Si-based intermetallic compounds 2f, 4f, and 3j, which are microstructures, can be measured by a nanoindenter.
[0059] The hardness measurement using a nanoindenter is based on "ISO 14577-1Metallic materials-Instrumented indentation test for hardness and materials parameters-" and its supplementary provisions "Annex A (normative) Materials parameters determined from the force / indentation depth data set". The hardness measurement using a nanoindenter uses a HYSITRONTI980 device manufactured by BRUKER.
[0060] The measurement conditions and measurement procedure of nanoindentation hardness are shown below.
[0061] Nanoindentation measurement conditions are as follows:
[0062] Test load: 800μN
[0063] Load: 1s
[0064] Hold: 0.4s
[0065] Uninstall: 1s
[0066] The ISO description of the test conditions is as follows:
[0067] HIT=HIT8×10 -4 / 1 / 0.4 / 1(Note: ISO 14577-1Annex A)
[0068] The measurement procedure and the method for determining the nanoindentation hardness of the Cr-Fe-Si system intermetallic compounds 2f, 4f and 3j are as follows.
[0069] 1. Grind the sample surface using an ion milling device to form a smooth surface.
[0070] 2. Use SEM / EDS to confirm the components in the field of view containing the Cr-Fe-Si intermetallic compounds 2f, 4f, and 3j. Next, use the camera of the nanoindentation measuring device to confirm that the field of view is the same as that of the Cr-Fe-Si intermetallic compounds 2f, 4f, and 3j. Thus, the field of view of the nanoindentation measurement is determined.
[0071] 3. In a 13.5 μm×13.5 μm field of view including the Cr—Fe—Si intermetallic compounds 2f, 4f, and 3j, a grid with a grid spacing of 1.5 μm was set, and the nanoindentation hardness of a total of 100 grid points in the grid was sequentially measured under the above nanoindentation measurement conditions.
[0072] 4. Based on the above measurement results, a contour map is obtained by connecting points of the same nanoindentation hardness with lines. Fig. 6A The contour map is obtained by connecting points of equal hardness with lines. Fig. 6A The peak of the nanoindentation hardness is obtained by taking a contour section on a line parallel to the X-axis (D-D' in FIG6 ). Figure 6B It is a cross-sectional view showing the hardness distribution obtained by taking a cross section of contour lines.
[0073] 5. Figure 6B In the hardness profile diagram, A represents the region of the matrix 2e, 4e and 3i, B represents the boundary region between the matrix 2e, 4e and 3i and the Cr-Fe-Si system intermetallic compounds 2f, 4f and 3j, and C represents the region of the Cr-Fe-Si system intermetallic compounds 2f, 4f and 3j.
[0074] The nanoindentation hardness in region A of the matrix 2e, 4e and 3i is about 4 GPa. In the boundary region B between the matrix 2e, 4e and 3i and the Cr-Fe-Si intermetallic compounds 2f, 4f and 3j, the Cr-Fe-Si intermetallic compounds 2f, 4f and 3j are crystallized, and thus the hardness is greater than that of the matrix 2e, 4e and 3i. The hardness begins to rise sharply from the peripheral part close to the matrix 2e, 4e and 3i. In region C of the Cr-Fe-Si intermetallic compounds 2f, 4f and 3j, the nanoindentation hardness of the center is relatively flat. Figure 6B The nanoindentation hardness is 19.5 GPa or more and 24.4 GPa or less.
[0075] In this measurement method, the nanoindentation hardness can only obtain discrete values. Therefore, as a method of expressing the hardness of the Cr-Fe-Si intermetallic compounds 2f, 4f and 3j, the high hardness region C with a flat center is regarded as the region where the Cr-Fe-Si intermetallic compounds 2f, 4f and 3j are crystallized. Then, the nanoindentation hardness of the region C is used as the hardness of the Cr-Fe-Si intermetallic compounds 2f, 4f and 3j.
[0076] In addition, when determining the boundary region B, the nanoindentation hardness of a certain grid point is set to H n The nanoindentation hardness of adjacent grid points with a distance of 1.5 μm is set as H n+1 In the case of |H n+1 -H n The portion with the condition of |>6.0 GPa is defined as boundary region B, and the boundary line between regions C and B is set according to the contour line.
[0077] The region C determined in this way, where the hardness is greater than that of the boundary region B, is regarded as a region where the Cr-Fe-Si system intermetallic compounds 2f, 4f and 3j are crystallized. Figure 6B In the case of the Cr—Fe—Si-based intermetallic compounds 2f, 4f, and 3j shown, the nanoindentation hardness of the region C is 19.5 GPa or more and 24.4 GPa or less.
[0078] In addition, the measurement of nanoindentation hardness may also reflect multiple fields of view (for example, 5 fields of view). In this case, the nanoindentation hardness of each of fields of view 1 to field of view 5 is set from the minimum value to the maximum value as the nanoindentation hardness of Cr-Fe-Si intermetallic compounds 2f, 4f and 3j. In addition, the measurement steps to determination methods of the nanoindentation hardness of other intermetallic compounds are also performed in the same process.
[0079] The cam bracket sliding material 2b, cam driver sliding material 4b, cam bracket side cam slider sliding material 3f and cam driver side cam slider sliding material 3g of the embodiment respectively improve sliding properties through the three-dimensional bonding structure of particles and nanoindentation hardness of Cr-Fe-Si based intermetallic compounds 2f, 4f, and 3j.
[0080] The composition, structure, three-dimensional structure, and nanoindentation hardness of the cam bracket sliding material 2b, cam driver sliding material 4b, cam bracket side cam slider sliding material 3f, and cam driver side cam slider sliding material 3g of the embodiment are compared with those of the sliding materials of the comparison example, and the effects of the cam bracket sliding material 2b, cam driver sliding material 4b, cam bracket side cam slider sliding material 3f, and cam driver side cam slider sliding material 3g of the embodiment are confirmed.
[0081] The cam bracket sliding material 2b, cam driver sliding material 4b, cam bracket side cam slider sliding material 3f and cam driver side cam slider sliding material 3g of the embodiment have a (Cr,Fe)3Si structure in the brass-based casting alloy blanks 2e, 4e and 3i respectively, and have a three-dimensional structure composed of a curved surface with rounded corners and partially connected with Cr-Fe-Si intermetallic compounds 2f, 4f, and 3j, and the nanoindentation hardness has a hardness of more than 20 GPa and less than 28 GPa.
[0082] Among the intermetallic compounds composed of Cr, Fe, and Si, there are Cr-Fe-Si intermetallic compounds 2f, 4f, and 3j, which are (Cr,Fe)3Si (specifically, (Cr 0.85 Fe 0.15 )3Si), Fe-Cr-Si intermetallic compounds with Fe as the main component (Fe,Cr)3Si (specifically, (Fe0.85 Cr 0.15 However, these two intermetallic compounds show completely different morphologies.
[0083] Cr-Fe-Si intermetallic compounds 2f, 4f and 3j and Fe-Cr-Si intermetallic compounds have a tendency to crystallize simultaneously. In order to effectively utilize only Cr-Fe-Si intermetallic compounds, the inventors attempted to separate and solidify these two silicides. As a result, by controlling the solidification conditions, Cr-Fe-Si intermetallic compounds 2f, 4f and 3j and Fe-Cr-Si intermetallic compounds were successfully separated and solidified. As a result, the excellent friction and wear characteristics specialized for Cr-Fe-Si intermetallic compounds can be grasped, and the embodiment can be realized.
[0084] Even if the intermetallic compounds have the same Cr, Fe, and Si as constituent components, the morphology and nanoindentation hardness of the Cr-Fe-Si intermetallic compounds 2f, 4f, and 3j and the Fe-Cr-Si intermetallic compounds are completely different, and as a result, the friction and wear performance brought by the hard compounds is different. In the embodiment, for the purpose of effectively utilizing the Cr-Fe-Si intermetallic compounds 2f, 4f, and 3j, the Cr-Fe-Si intermetallic compounds 2f, 4f, and 3j are characterized in that they have a three-dimensional structure in which Cr is the main component and is composed of curved surfaces with rounded corners and partially connected.
[0085] In the brass-based cast alloy, wear resistance and low friction (low μ property) were evaluated according to the tribological basic formula (1).
[0086] μ=τ0 / P H ···(1)
[0087] Where, μ: friction coefficient, τ0: shear force of lubricating material, P H : Hardness (load / area).
[0088] The friction coefficient μ is proportional to the shear force of the lubricant and inversely proportional to the hardness of the substrate. H It is the value obtained by dividing the load by the contact area. In order to reduce the friction coefficient μ, it is necessary to increase the hardness of the intermetallic compound, which is the load point during friction, and reduce the contact area of the intermetallic compound.
[0089] That is, the shape of the compound is preferably close to a spherical shape so as to reduce the contact area, and if the compound is a hard compound, the friction coefficient can be reduced.
[0090] Figure 4 and Figure 5 Cr-Fe-Si intermetallic compounds 2f, 4f and 3j according to the embodiment are shown. Figure 4 and Figure 5 As shown, the Cr-Fe-Si based intermetallic compounds 2f, 4f and 3j of the embodiment are in the form of compounds composed of hard, rounded curved surfaces connected to each other.
[0091] Therefore, it can be said that the Cr-Fe-Si based intermetallic compounds 2f, 4f and 3j of the embodiment are hard, have a reduced friction surface, and have an increased heat dissipation area, which is a form capable of reducing the friction coefficient.
[0092] Figure 7 The Fe-Al intermetallic compound of Comparative Example 2 is shown. Figure 7 As shown, the Fe—Al-based intermetallic compound of Comparative Example 2 is square, and the compounds are not independently connected.
[0093] The effect of the Cr-Fe-Si intermetallic compounds 2f, 4f and 3j of the embodiment is that, according to the above tribological basic formula (1), P H The increase in (hardness) reduces the friction coefficient, and the interposition of the lubricant reduces the friction work represented by μ×load×speed, thereby reducing the generation of frictional heat and exerting a low friction effect.
[0094] The wear amount (V) of the sliding material is expressed by equation (2).
[0095] V=Z(P / P H )L···(2)
[0096] The wear volume (V) is proportional to the wear coefficient Z, load P, and friction distance L, and is also proportional to the hardness P. H Therefore, by increasing the hardness of the compound crystallized in the soft brass casting alloy, the wear amount can be reduced.
[0097] Region C ( Fig. 6A , Figure 6B The nanoindentation hardness of the nanostructured carbon steel is 20 GPa to 28 GPa, which is a structure with excellent wear resistance.
[0098] During friction, the intermetallic compound becomes a load point, generating strong friction heat. This friction heat is dissipated through the interface between the intermetallic compound and the copper alloy matrix. Therefore, by connecting the compounds three-dimensionally, the surface area of the intermetallic compound as a whole can be increased, and the heat dissipation efficiency can be greatly improved. In this way, the heat dissipation efficiency during friction is good, the rise of surface temperature can be prevented, and the severe friction conditions can be alleviated.
[0099] For example, when the Fe-Al intermetallic compound of the comparative example of single crystal granules becomes a load point and the friction heat increases, the temperature of the intermetallic compound increases, the compound / matrix interface softens, and there is a possibility that the compound interface becomes unstable and dissociates.
[0100] On the other hand, Figure 4 and Figure 5 As shown, the surface area of the Cr-Fe-Si intermetallic compounds 2f, 4f and 3j of the embodiment is large and connected, so the heat exchange area is increased, and the friction heat generated by the concentrated load can be appropriately diffused. Such a three-dimensional structure is an important element in the field of friction and wear.
[0101] Thus, the shape and continuity of the Cr-Fe-Si intermetallic compounds 2f, 4f and 3j are of great significance, and they function effectively as high-load sliding materials. That is, the continuity and hardness of the Cr-Fe-Si intermetallic compounds 2f, 4f and 3j can be said to be excellent structures that prevent wear and present a low friction state.
[0102] Hereinafter, evaluation examples of the present invention will be described. In addition, the present invention is not limited to the following evaluation examples.
[0103] The structures of the intermetallic compounds contained in the sliding materials of the embodiment (the cam support sliding material 2b, the cam driver sliding material 4b, the cam support side cam slider sliding material 3f, and the cam driver side cam slider sliding material 3g) and the sliding materials of the comparative example are shown in Table 1. The sliding materials of the embodiment 1 (the cam support sliding material 2b, the cam driver sliding material 4b, the cam support side cam slider sliding material 3f, and the cam driver side cam slider sliding material 3g) and the sliding materials of the comparative example 2 contain the intermetallic compounds shown in Table 1 in a brass-based cast alloy matrix of Cu-26Zn-5Al.
[0104] Example 1 is a sliding material (cam support sliding material 2b, cam driver sliding material 4b, cam support side cam slider sliding material 3f, and cam driver side cam slider sliding material 3g) in which Cr-Fe-Si intermetallic compounds (2f, 4f, and 3j) are crystallized in the matrix (2e, 4e, and 3i), respectively. Comparative Example 2 is a sliding material in which Fe-Al intermetallic compounds are crystallized in the matrix, and is a commonly used high-strength brass material.
[0105] Table 1 shows the chemical formula of each intermetallic compound, the crystal form of the intermetallic compound (the shape of the intermetallic compound, the continuity (bonding, connection) of the intermetallic compound), and the nanoindentation hardness (GPa). In addition, the addition amount of Si in Example 1 was set to 0.3%, and the addition amounts of Mn, Fe, Cr, etc. were determined according to the composition of the crystallized compound.
[0106] [Table 1]
[0107]
[0108]
[0109] All alloys are first melted at a melting temperature of 1100°C, pure Cu ingots are then added to produce Cu-Zn alloys, Al is then added, melted, and then heated to 1200°C, and a master alloy of elements required for melting is added, melt-casting is performed in a manner to obtain a predetermined composition, and processed into a test piece shape. In addition, the sliding material of the present embodiment can also be produced by a sand casting method, a metal mold casting method, and a processing method of performing extrusion processing and drawing processing after metal mold casting, and is not limited to each manufacturing method.
[0110] In the case of the Cr-Fe-Si intermetallic compounds (2f, 4f, and 3j) of Example 1, a region with a nanoindentation hardness of 19.5 GPa or more and 27.9 GPa or less was observed in the field of view including the Cr-Fe-Si intermetallic compounds (2f, 4f, and 3j). On the other hand, in the case of the Fe-Al intermetallic compounds of Comparative Example 2, a region with a nanoindentation hardness of 6.6 GPa or more and 7.4 GPa or less was observed.
[0111] Thus, the Cr-Fe-Si based intermetallic compounds (2f, 4f and 3j) of Example 1 are extremely hard intermetallic compounds, and the hardness has a great influence on the friction performance.
[0112] Figure 8 The following is an overview of a reciprocating sliding test device. The wear amount can be measured using a so-called pin-disc type reciprocating sliding test device. 1 in the figure represents a pressurizing device, 2 represents the test material, and 3 represents the other material. 4 is a motor that causes the other material to reciprocate. The following are test conditions.
[0113] Testing machine: reciprocating load testing machine
[0114] Maximum sliding speed: 8m / min
[0115] Reciprocating sliding distance: 150mm
[0116] Total sliding distance: 500m
[0117] Test temperature (bearing back temperature): 100°C
[0118] ·Material of the other party: FC250, surface roughness Ra3.0
[0119] Lubricant: VG32
[0120] Wear test load: 30MPa constant load
[0121] Fig. 9 The wear amount of the sliding materials of Example 1 (cam holder sliding material 2b, cam driver sliding material 4b, cam holder side cam slider sliding material 3f, and cam driver side cam slider sliding material 3g) and Comparative Example 2 are shown. In addition, the wear amount in Example 1 is 2μm. On the other hand, in Comparative Example 2, the wear amount is 20μm.
[0122] The sliding materials of Example 1 (cam bracket sliding material 2b, cam driver sliding material 4b, cam bracket side cam slider sliding material 3f and cam driver side cam slider sliding material 3g) can obtain exceptionally excellent wear resistance compared to the sliding materials of Comparative Example 2 used in the past.
[0123] In this way, it is confirmed that the sliding materials of the embodiment (cam bracket sliding material 2b, cam driver sliding material 4b, cam bracket side cam slider sliding material 3f, and cam driver side cam slider sliding material 3g) can obtain excellent improvement in friction performance through the crystallization of Cr-Fe-Si based intermetallic compounds (2f, 4f, and 3j) with excellent tribological properties in terms of crystal morphology and nanoindentation hardness.
[0124] Next, the sliding material of Example 1 (cam support sliding material 2b and cam actuator sliding material 4b) and the sliding material of Comparative Example 2 were assembled in Figure 1 In the cam device shown, the cam device is used as a function of Fig.10 The test device shown in the figure is used for evaluation. In the figure, 1 represents a cam unit, 9 represents a load air cylinder, 10 represents an upper die, and 11 represents a lower die. In addition, the strike return test is a test method that uses a punching device to simulate actual die processing.
[0125] The following are the test conditions for the impact reset test. In addition, the impact reset number indicates the number of times the punching action is performed. The slider of the punching machine descends from the top dead center, presses the upper die of the die down to the bottom dead center, activates the cam device, and returns to the original top dead center. This is the number of actions in one cycle, also known as the impact number.
[0126]
[0127] Generally, it is believed that the wear curve is divided into two regions: I) the initial wear region where the wear is rapid during the running-in stage, and II) the stable wear region where the running-in surface is formed and the wear rate is slowed down. In the initial wear stage, the machined surface containing the machining error slides, thereby rapidly generating the necessary wear and forming the best running-in surface in the device. By eliminating the initial wear stage in advance, the sliding between the running-in surfaces becomes stable, the wear amount is slowed down, and a stable friction state is entered. By comparing the wear curves, the characteristics of each sliding material can be known. In addition, the initial wear region is defined as the region with a strike reset number of 0 to 5000 times, and the stable wear region is defined as a stable region after the strike reset number is 20,000 times.
[0128] The test results are shown in Fig.11 , Fig.12 The test results are shown in a wear curve with the vertical axis representing the amount of wear and the horizontal axis representing the number of strike resets. In this test, the number of strike resets was increased to 50,000 times, and the wear curves of the cam support sliding material and the cam driver sliding material of Example 1 and Comparative Example 2 were measured.
[0129] It can be seen that the cam support sliding material 2b ( Fig.11 )、Cam driver sliding material 4b( Fig.12 ) are transferred to the stable wear state (20000 times~) after the initial wear (~5000 times) ( Fig.11 , Fig.12 2 lines in the figure). Fig.12 As shown, for the wear amount when reset after 50,000 hits, Comparative Example 2 ( Fig.12 The cam actuator sliding material of the embodiment 1 (1 line) is 17.8 μm. Fig.12 The cam drive sliding material 4b of line 2 in FIG. 1 is 4.9 μm. Fig.11 As shown, for the wear amount when reset after 50,000 hits, Comparative Example 2 ( Fig.11 The cam support sliding material of the 1st line in the embodiment is 12.7μm. Fig.11 The cam support sliding material 2b of the cam drive sliding material 2b is 4.4 μm. It can be seen that both the cam support sliding material 2b and the cam drive sliding material 4b are much smaller in Example 1 than in Comparative Example 2. Surprisingly, the wear rate is also reduced in both the initial wear area and the stable wear area.
[0130] Table 2 shows the wear rate of the initial wear region and the stable wear region of the cam actuator sliding material 4b. In the initial wear region from 0 to 5000 strokes, the material of the present application in which the hard compound shown in Table 1 is precipitated shows a wear rate of 6.8 μm / 10 4The wear rate of the comparative material with soft compound precipitation is 30.0μm / 10 4 The wear rate is about 4.4 times of the reset of the first strike. In addition, it is found that even in the stable wear area where the wear amount is stable, the material of the present application is stable at an extremely low wear rate, while the comparative example wears at a rate of about 4.3 times. In this way, in the cam device using the sliding material of the embodiment (cam bracket sliding material 2b and cam driver sliding material 4b), excellent wear resistance is confirmed in both the initial wear area and the stable wear area.
[0131] [Table 2]
[0132]
[0133] The cam device of the embodiment is a cam device as follows: a solid lubricant is embedded in the sliding surface, a sliding material (cam holder sliding material 2b, cam driver sliding material 4b, cam holder side cam slider sliding material 3f and cam driver side cam slider sliding material 3g) containing a Cr-Fe-Si system intermetallic compound having a nanoindentation hardness of 20 GPa or more and 28 GPa or less is provided in the brass-based cast alloy matrix, and the sliding material is 20.0 (N / mm 2 ) or more, the wear rate of the sliding materials (cam support sliding material 2b, cam driver sliding material 4b, cam support side cam slider sliding material 3f, and cam driver side cam slider sliding material 3g) in the stable wear area is 0.20 (μm / 10 4 Hit reset) or less.
[0134] The cam device of the embodiment is a cam device as follows: a solid lubricant is embedded in the sliding surface, a sliding material (cam holder sliding material 2b, cam driver sliding material 4b, cam holder side cam slider sliding material 3f and cam driver side cam slider sliding material 3g) containing a Cr-Fe-Si system intermetallic compound having a nanoindentation hardness of 20 GPa or more and 28 GPa or less is provided in the brass-based cast alloy matrix, and the sliding material is 20.0 (N / mm 2 ) or above, the wear rate of the sliding materials (cam support sliding material 2b, cam driver sliding material 4b, cam support side cam slider sliding material 3f, and cam driver side cam slider sliding material 3g) in the initial wear area is 8.0μm / 10 4 Hit again to reset.
[0135] The cam device of the embodiment is a cam device as follows: a solid lubricant is embedded in the sliding surface, a sliding material (cam holder sliding material 2b, cam driver sliding material 4b, cam holder side cam slider sliding material 3f and cam driver side cam slider sliding material 3g) containing a Cr-Fe-Si system intermetallic compound with a nanoindentation hardness of 20 GPa or more and 28 GPa or less is provided in the brass type cast alloy matrix, and the sliding material is 20.0 N / mm 2 Under the above surface pressure, the wear loss of the sliding material after 50,000 impacts and resets is less than 5.0μm.
[0136] Generally, on a panel (1 mm thick) with a material strength of 780 MPa, which is called high-strength steel, the largest fastener (shank diameter) that can be set on a 46 mm wide cam is used. ) is processed and the blanking force during processing is calculated. As a result, the surface pressure applied to the cam bracket sliding surface 2a is calculated to be 19.1 MPa. In the cam device 1 of the embodiment, the high processing force is the surface pressure applied to the sliding surface exceeding 20 MPa.
[0137] [Table 3]
[0138]
[0139]
[0140] That is, it is found that the sliding materials of the embodiment (cam bracket sliding material 2b, cam driver sliding material 4b, cam bracket side cam slider sliding material 3f and cam driver side cam slider sliding material 3g) are applied to the cam device 1 and can also withstand high loads (above 20MPa) and only suffer extremely small wear, thereby maintaining high-precision processing.
[0141] The cam device involved in the embodiment is not limited to the above-mentioned example. For example, in the cam device shown in the embodiment, the cam holder and the cam driver are assembled as components separate from the mold, but are not limited to this separate structure. For example, either the cam holder or the cam driver may be integrated with the mold. If the cam driver and the mold are integrated, the mold has the function of a cam driver.
[0142] For example, the cam device has an upper hanging cam ( Figure 1 The cam device 1 shown in the figure includes a bottom-placed cam, a roller cam, etc., and the structures are different. Any cam has a sliding portion, and the sliding material of the cam device of the embodiment can be applied to each sliding portion. As a result, it can become a cam device with improved wear resistance and durability and high processing power.
[0143] Hereinafter, application examples of the cam device 1 of the embodiment will be described. The cam device of the embodiment can be, for example, a bottom-mounted cam device or a roller cam device described below. In addition, descriptions of well-known structures of each cam device are appropriately omitted.
[0144] Fig.13 The exploded view of the bottom-placed cam device 200 is shown. The cam device 200 includes a cam driver 201, a cam slider 202, a cam bracket 203, and a restoring elastic member 207. The cam driver 201 is mounted on the upper die of the stamping die device and drives the cam slider 202 in the processing direction. The cam bracket 203 is mounted on the lower die. The cam slider 202 can be provided with a processing tool for processing a workpiece and is slidably mounted on the cam bracket 203.
[0145] like Fig.13 As shown, a sliding material 201a having a sliding surface 201b is detachably provided on the cam driver 201. The cam slider 202 has a sliding surface 202a that is in sliding contact with the sliding surface 201b, a tool mounting surface 202b, a sliding surface 202c, and a sliding surface 202d. The cam bracket 203 has a sliding surface 203a that is in sliding contact with the cam slider 202.
[0146] For example, the sliding material of any one of the sliding parts of the cam driver 201, the sliding part of the cam slider 202, and the sliding part of the cam bracket 203 comprises: a substrate, which is composed of a brass-based cast alloy; and a Cr-Fe-Si-based intermetallic compound, which is contained in the substrate and the nanoindentation hardness of the area where the Cr-Fe-Si-based intermetallic compound is exposed is 20 GPa or more and 28 GPa or less, and also has a solid lubricant embedded in the substrate, which has a nanoindentation hardness of 20.0 N / mm 2 Under the surface pressure above 0.20 μm / 10 4 The cam device 200 having high processing force and excellent sliding property can be realized by performing the reset operation after one strike.
[0147] Furthermore, the sliding material of any one or more of the sliding parts of the cam driver 201, the sliding part of the cam slider 202, and the sliding part of the cam bracket 203 further has a solid lubricant embedded in the matrix, and the sliding material has a lubrication resistance of 20.0 N / mm 2 Under the above surface pressure, the wear rate of the initial wear area of the sliding material is 8.0μm / 10 4 The cam device 200 has high processing force and excellent sliding properties. 2 Under the above surface pressure, a cam device can be provided in which the wear amount of the sliding material is less than 5.0μm when the sliding material is reset 50,000 times.
[0148] Fig.14 An exploded view of a roller-type cam device 300 is shown. The cam device 300 includes a cam holder 301 fixed to a fixed mold (lower mold, not shown) or the like; a cam slider 302 slidably supported on the cam holder 301; and a cam driver 303 fixed to a movable mold (upper mold, not shown) or the like, for driving the cam slider 302 in a predetermined processing direction A. The cam slider 302 is urged in the return direction by a restoring elastic member 306, and reciprocates in the processing direction A with a predetermined stroke, and a processing tool (not shown) is mounted on the side.
[0149] like Fig.14 As shown, the cam holder 301 has sliding materials 301a, 301b, 301c, and 301d for enabling the cam slider 302 to move in a predetermined processing direction A.
[0150] like Fig.14 As shown, the cam slide 302 has a roller 304 .
[0151] For example, the sliding material of any one or more of the sliding parts 301a, 301b, 301c, 302d of the cam bracket 301 and the roller 304 of the cam slider 302 comprises: a substrate composed of a brass-based cast alloy; and a Cr-Fe-Si-based intermetallic compound, wherein the nanoindentation hardness of the region in which the Cr-Fe-Si-based intermetallic compound is exposed and contained in the substrate is 20 GPa or more and 28 GPa or less, and a solid lubricant embedded in the substrate and having a hardness of 20.0 N / mm 2 Under the surface pressure above 0.20 μm / 10 4 The cam device 300 having excellent sliding properties can be realized by performing the reset operation once or less.
[0152] Furthermore, the sliding material of any one or more of the sliding parts 301a, 301b, 301c, 302d of the cam holder 301 and the roller 304 of the cam slider 302 further has a solid lubricant embedded in the matrix, which is 20.0N / mm 2 Under the above surface pressure, the wear rate of the initial wear area of the sliding material is 8.0μm / 10 4 The cam device 300 can be realized with high processing force and excellent sliding property. 2 Under the above surface pressure, a cam device can be provided in which the wear amount of the sliding material is less than 5.0μm when the sliding material is reset 50,000 times.
[0153] Thus, the cam device of the embodiment can have a sliding material of various shapes (for example, a plate shape, a cylindrical shape) in the sliding portion, and can be applied to the cam device 1 ( Figure 1 ) Cam device 200 with different structures ( Fig.13 )、Cam device 300( Fig.14 ).
[0154] The above embodiments are described, but the embodiments are presented only as examples and are not intended to limit the scope of the invention. The novel embodiments can be implemented in various other ways, and various omissions, substitutions, and changes can be made without departing from the scope of the invention. The embodiments and their variations are included in the scope and spirit of the invention, and are included in the invention described in the claims and the scope of their equivalents.
[0155] Explanation of symbols
[0156] 1: Cam device 1
[0157] 2: Cam bracket
[0158] 3: Cam slider
[0159] 4: Cam drive
[0160] 5: Elastic components for recovery
Claims
1. A cam device comprising a sliding material, wherein the sliding material has: a substrate composed of a brass-based casting alloy; and A Cr—Fe—Si based intermetallic compound is contained in the matrix, and a nanoindentation hardness of a region where the Cr—Fe—Si based intermetallic compound is precipitated is 20 GPa or more and 28 GPa or less.
2. The cam device according to claim 1, wherein: The sliding material further comprises a solid lubricant embedded in the matrix. The sliding material in the impact reset test is 20.0N / mm 2 Under the surface pressure above 100°, the wear rate of the initial wear area of the sliding material is 8.0 μm / 10 4 Hit again to reset.
3. The cam device according to claim 1 or 2, wherein: The sliding material further comprises a solid lubricant embedded in the matrix. The sliding material in the impact reset test is 20.0N / mm 2 Under the surface pressure above 0.20 μm / 10 4 Hit again to reset.
4. The cam device according to claim 3, wherein: The wear rate of the stable wear region of the sliding material is more preferably 0.10 μm / 10 4 Hit again to reset.
5. The cam device according to any one of claims 1 to 4, wherein: The sliding material further comprises a solid lubricant embedded in the matrix. The sliding material in the impact reset test is 20.0N / mm 2 Under the above surface pressure, the wear amount of the sliding material is less than 5.0 μm when it is impacted and reset 50,000 times.
6. The cam device according to any one of claims 1 to 5, wherein: The cam device comprises: a cam support having a cam support slide; a cam slider having a cam driver side cam slider sliding portion and a cam holder side cam slider sliding portion in sliding contact with the cam holder sliding portion; and a cam driver having a cam driver sliding portion in sliding contact with the cam driver side cam slider sliding portion, Wherein, the sliding material is at least one of the cam support sliding part, the cam driver sliding part, the cam support side cam slider sliding part and the cam driver side cam slider sliding part.
7. The cam device according to any one of claims 2, 3 and 5, wherein: The solid lubricant is graphite.
8. The cam device according to any one of claims 1 to 7, wherein: The Cr-Fe-Si system intermetallic compound has a three-dimensional structure formed by connecting the Cr-Fe-Si system intermetallic compounds, has a shape consisting of curved surfaces with rounded corners, and has a chemical structure of (Cr, Fe) 3 Si.
9. The cam device according to any one of claims 1 to 8, wherein: The cam device is not only an upper hanging type cam device, but also a lower placement type cam device or a roller type cam device.
Citation Information
Patent Citations
High-tensile brass alloy for sliding member and sliding member
JP2010265500A
Cam device
JP2011140048A
Cam device
JP2015027702A